2011
DOI: 10.1007/s10526-011-9385-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Arachnida alien to Europe

Abstract: The ecology of selected species of spiders (Araneae), harvestmen (Opiliones), and the neglected tropical order Schizomida, alien to Europe, is discussed. Their geographic origins and pathways of introduction, by transportation with goods, are similar to other predatory terrestrial arthropods. Occurrence in buildings (synanthropy) is a prerequisite for range expansion in many arachnid species. Thelytokous parthenogenesis facilitated spread of a few spider, harvestman and schizomid species outside their native r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Whilst these examples do not all provide subsequent evidence of establishment of the alien species in the new region (which is dependent on many factors, including the number of beetles transported and climatic and habitat suitability in the new area), they clearly illustrate that accidental anthropogenic transport can be an important mechanism for the spread of invasive alien species such as H. axyridis. Nedvěd et al (2011) outlined similar mechanisms involved in the spread of arachnids in Europe and North America. Some of the examples also indicate that H. axyridis is a species that is robust enough to survive very long journeys, and that its aggregative behaviour at certain times of the year is potentially an important feature in terms of dispersal.…”
Section: The Influence Of Abiotic Factors On Dispersalmentioning
confidence: 99%
“…Whilst these examples do not all provide subsequent evidence of establishment of the alien species in the new region (which is dependent on many factors, including the number of beetles transported and climatic and habitat suitability in the new area), they clearly illustrate that accidental anthropogenic transport can be an important mechanism for the spread of invasive alien species such as H. axyridis. Nedvěd et al (2011) outlined similar mechanisms involved in the spread of arachnids in Europe and North America. Some of the examples also indicate that H. axyridis is a species that is robust enough to survive very long journeys, and that its aggregative behaviour at certain times of the year is potentially an important feature in terms of dispersal.…”
Section: The Influence Of Abiotic Factors On Dispersalmentioning
confidence: 99%
“…Roura-Pascual et al (2011) found that climatic suitability and the extent of human modification of habitats are primarily responsible for the global distribution of the Argentine ant. Kobelt and Nentwig (2008) found greater than expected numbers of introductions of alien spiders to Europe from the eastern Palearctic and Indomalayan versus other geographic regions (see also Nedved et al 2011). The authors attribute this pattern in part to the relatively similar climates of these regions and Europe.…”
Section: Climate and Its Changementioning
confidence: 85%
“…There are many studies focused on different invasive and expansive species of animals and plants (Keller et al, 2011;Staska et al, 2014;Hoofman et al, 2006), cause their potential (socio)economic importance (Holmes et al, 2009;Oreska and Aldridge, 2011). From that perspective, spiders belong among well studied groups (Nentwig and Kobelt, 2010;Nedvěd et al, 2011). The common wall spider, Brigittea civica (Lucas, 1850) is not medically or really economically important, but is known to pollute the faces of buildings (Billaudelle 1957, Hertel 1968.…”
Section: Introductionmentioning
confidence: 99%